Factor V Q506 Mutation (Activated Protein C Resistance) Associated with Reduced Intrapartum Blood Loss – a Possible Evolutionary Selection Mechanism - Lindqvist, Pelle G.; Svensson, Peter J.; Dahlbäck, Björn; Maršál, Karel (Thrombosis and Haemostasis, 1998)
Objectives. To ascertain whether relationship exists between the presence of APC resistance [a hypercoagulable state due to a mutation (R506Q) in the factor V gene] and the occurrence of pre-eclampsia (PE), intrauterine growth retardation (IUGR), and pregnancy bleeding complications. Design. A retrospective study. Subjects. A study group of 122 women with PE and/or IUGR during a recent pregnancy and a control group of 465 healthy pregnant women. Results. A significantly reduced risk of intrapartum bleeding complications in the APC-resistant subgroup as compared to the non-APC-resistant subgroup was suggested by reduced intrapartum blood loss, and pre- and postpartum haemoglobin measurements. The prevalence of APC resistance in the PE and IUGR subgroups did not differ significantly from that in the control group. Conclusion. The remarkably high prevalence of the potentially harmful factor V gene mutation in the general population may be the result of an evolutionary selection mechanism conferring such survival advantages as reduction in the risk of intrapartum bleeding on carriers of the FV:Q506 allele.